Current Surgical Management of Hidradenitis Suppurativa: A Systematic Review and Meta-Analysis. Issue 3 (11th March 2021) - Riddle, Ashley; Westerkam, Linnea; Feltner, Cynthia; Sayed, Christopher
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Hidradenitis suppurativa (HS) is a chronic dermatologic condition that often necessitates surgical treatment. Surgical approaches vary substantially with little data on efficacy and safety. OBJECTIVE: Summarize the literature on HS surgery with regards to patient characteristics, surgical approaches, and study quality. Compare postsurgical recurrence rates with a meta-analysis. Methods: PubMed, Embase, and Scopus were searched for studies on surgical HS management published after 2004. A random effects meta-analysis of recurrence rates was performed on eligible studies. Results: Of 715 identified studies, 59 were included in the review and 33 in the meta-analysis. Twenty-two studies of wide excision had the lowest pooled recurrence rate at 8% (95% confidence interval [CI] 2%–16%); local excision had the highest at 34% (95% CI 24%–44%). For studies of wide/radical excision, flap repair had the lowest pooled recurrence rate at 0% (95% CI 0%–4%); delayed primary closure had the highest at 38% (95% CI 20%–59%). Conclusions: Wide excision and flap-based reconstruction are associated with a lower postsurgical HS recurrence, although this must be balanced against potentially higher morbidity of extensive procedures. Heterogeneity and methodological limitations of the evidence limit the ability to make a strong conclusion about the relative recurrence rates associated with surgical techniques. Registration: PROSPERO ID: CRD42020159948.